Arc voltage measurements for height control in pulsed arc additive manufacturing. (15th March 2022) - Xiong, Jun; Yu, Yongsheng; Zheng, Senmu; Zhang, Guangjun
Graphical abstract: Highlights: Arc voltage is intended for characterizing height stability in P-GTA AM. An EMD algorithm is developed for filtering noises in pulsed arc voltage. A fuzzy logic PID controller is designed to control peak voltage for improving height stability. Abstract: Pulsed-gas tungsten arc additive manufacturing (P-GTA AM) is highly suitable for producing high-performance and large-size components. However, research work concerning monitoring and control to increase process automation and steadiness is extremely inadequate. Aiming at a stable deposition in P-GTA AM, an arc voltage (AV) measuring and feedback control strategy is proposed. The novelty is that noises in pulsed AV are removed via an empirical mode decomposition denoising method and the peak AV is determined as the optimal feedback signal to characterize height variations by conducting static and dynamic tests. A fuzzy logic PID controller is designed to control the peak AV by regulating the amount of filler wire. Thin walls are manufactured to check the controller's robustness, and the application of the control system through feedback from AV measurements can excellently ensure stable deposition height in P-GTA AM with a maximum AV deviation of 0.4 V.